Ethnobotany of Ancak Cooking Ingredients by Madurese Ethnic in Kalipuro and Gombengsari Village, Banyuwangi - Shafyan Khairus Shaleh; Luchman Hakim; Dian Siswanto (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
This study aims to identify the types of spices used in Ancak cuisine, and to describe the composition and basic ingredients. The research methods included field surveys and in-depth interviews, which were analyzed using an ethnobotanical approach. The level of plant utilization was analyzed using Use Values (UVs), and the frequency of use based on cultural importance was measured using Index of Cultural Significance (ICS), while the frequency of mention of plant types was analyzed using Relative Frequency of Citation (RFC). The results show that there are 19 types of spice plants used in Ancak cuisine. The highest UVs value is found in Tamarindus indica with a value of 6, followed by Cinnamomum verum with a value of 5 and Myristica fragrans with a value of 2. The highest ICS values for spice plants are found in Allium cepa and Allium sativum at 30, and Zingiber officinale at 12. In addition, 20 types of plants were identified as ingredients and basic materials for making Ancak. The highest UVs value was found in Apium graveolens at 2, followed by Raphanus sativus var. hortensis and Nasturtium officinale at 1. The highest ICS value was found in Oryza sativa at 30, followed by Cocos nucifera at 9 and Allium fistulosum at 6. The highest RFC value was also found in Oryza sativa at 1, followed by Glycine max at 0.95, and Cucumis sativus at 0.35. These findings indicate that the Ancak dish reflects rich local ethnobotanical knowledge and strong social and cultural values.